Comparison of Central Corneal Thickness Changes After Phacoemulsification in Diabetic and Non-Diabetic Patients (Journal of National Institute of Ophthalmology, 2026)
Introduction: This prospective observational study investigates the impact of diabetes mellitus (DM) on central corneal thickness (CCT) after phacoemulsification cataract surgery. Cataract remains the principal cause of blindness, particularly in the developing world, and phacoemulsification is a widely practiced method for cataract surgery. The clarity of the cornea post-surgery is of great interest, as increased CCT can affect this clarity due to endothelial cell loss. Methodology: The study was conducted on 100 cataract patients undergoing phacoemulsification cataract surgery at the National Institute of Ophthalmology & Hospital, Dhaka, from July 2018 to January 2019. The patients were equally divided into diabetic and nondiabetic groups. Data on patients' ocular examination, endothelial cell count (ECC), and CCT were collected preoperatively and postoperatively on the 1st day, 7th day, and 1 month after surgery. The analysis was conducted using SPSS version 25, and the results were presented in tables and graphs. Results: The study revealed significant differences in CCT changes between the two groups. Diabetic patients exhibited greater CCT compared to nondiabetic patients postoperatively, indicating that hyperglycemia has a significant impact on corneal health. Specifically, the pre-operative mean CCT for diabetic patients was 528.80±2.08 μm, which increased to 540.16±5.53 μm on the 1st POD, 537.74±7.11 μm on the 7th POD, and 537.30±6.18μm after 1 month. In contrast, nondiabetic patients had a pre-operative mean CCT of528.98±9.45 μm, which changed to 541.64±15.56 μm on the 1st POD, 535.00±14.37 μm on the7th POD, and 534.42±13.45 μm after 1 month. Conclusion: The findings suggest that corneal changes in diabetic patients should be evaluated preoperatively to prevent postoperative corneal edema and maintain corneal clarity. This emphasizes the need for careful monitoring and management of diabetic patients undergoing phacoemulsification cataract surgery to ensure optimal postoperative outcomes.J.Natl.Inst.Ophthalmol.2024;7(2): 57-65